The The Wadī’ah and Murābaḥah Contracts in Islamic Banking: The Recognized and the Unrecognized Legally Transformation - Abdul Aziz, Jamal; Kholifah, Ayu (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The mu’āmalah fiqhiyyah contracts that underlie Islamic bank products have transformed from their basic form. Problems arise when there are differences in treating the same form of transformation. The purpose of this study is to construct the transformation of wadī’ah and murābaḥah contracts in savings and financing products at Islamic banks, then analyze them from the perspective of Islamic law. This research is qualitative, with the main data sources being literature and interviews with Islamic banking practitioners. Literature in the form of books and the results of previous research regarding contracts in Islamic bank products. The interviews were conducted with some managers of Islamic commercial banks (BSI Jakarta) and Islamic people’s financing banks (BPRS BAS Purwokerto). Data analysis was carried out by the triangulation method. Wadī’ah contracts in savings products and murābaḥah sales and purchase contracts in financing products at Islamic banks have essentially undergone the same transformation, which is both transformed into contracts with debt substance (qarḍ) where several procedural indicators corroborate this. However, it turns out that Islamic banks are different in responding to it. The transformation in the wadī’ah contract is recognized through the application of procedural provisions on the wadī’ah savings product, while the transformation in the murābaḥah contract is not recognized, which is indicated by the justification of the profit (murābaḥah) received by the bank. This research provides a new perspective on the study of the transformation of mu’āmalah contracts in Islamic bank products, which has so far been rarely carried out.